2022
DOI: 10.16920/jeet/2022/v36i1/22138
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management System Practices Performed in ISO 9001 Certified Engineering Educational Institutions: A Critical Analysis of Indian Universities

Abstract: This study aims to analyse the quality management system (QMS) practices performed in ISO 9001 certified engineering educational institutes of India. The literature divulged that QMS in engineering education mainly engrossed on teaching, learning, examinations, student results and infrastructure. Very few studies mentioned QMS in terms of organizational effectiveness. Thus the author has conducted the QMS analysis in forty-five engineering educational institutions (EEIs) of Delhi NCR area in India and selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The ISO quality management system includes eight principles of quality. Kansal (2022) analyzed the Quality Management system (QMS) practices implemented in ISO 9001 certified Indian engineering education institutions between two groups in the four (4) hotel technical institutes in Alexandria. Results showed that group B organizations scored significantly higher than Group A organizations and there were significant differences in the quality management system practices implemented between group A and Group B respondents.…”
Section: Student Performancementioning
confidence: 99%
“…The ISO quality management system includes eight principles of quality. Kansal (2022) analyzed the Quality Management system (QMS) practices implemented in ISO 9001 certified Indian engineering education institutions between two groups in the four (4) hotel technical institutes in Alexandria. Results showed that group B organizations scored significantly higher than Group A organizations and there were significant differences in the quality management system practices implemented between group A and Group B respondents.…”
Section: Student Performancementioning
confidence: 99%